Identification of Two Different 14-α Sterol Demethylase-Related Genes (cyp51A and cyp51B) in Aspergillus fumigatus and Other Aspergillus species - Mellado, E. (American Society for Microbiology, 2001)
Two cyp51-related genes (cyp51A and cyp51B) encoding 14-α sterol demethylase-like enzymes were identified in the opportunistic human pathogen Aspergillus fumigatus. PCR amplification using degenerate oligonucleotides based on conserved areas of cytochrome P450 demethylases of other filamentous fungi and yeasts allowed the cloning and sequencing of two different homologue genes in A. fumigatus. Southern analysis confirmed that both genes hybridized to distinct genomic loci and that both are represented as single copies in the genome. Comparison of the deduced Cyp51A and Cyp51B proteins with the CYP51 proteins from Penicillium italicum, Aspergillus nidulans, Erysiphe graminis, Uncinula necator, Botrytis cinerea, Ustilago maydis, Cryptococcus neoformans, Candida albicans, Saccharomyces cerevisiae, Candida tropicalis, and Candida glabrata showed that the percentages of identity of the amino acid sequences (range, 40 to 70%) were high enough to consider Cyp51A and Cyp51B to be members of the fungal CYP51 family. Fragments from both genes were also cloned from other Aspergillus spp. (A. flavus, A. nidulans, and A. terreus). Phylogenetic analysis showed that, at least in the most pathogenic species of Aspergillus, there are two fungal CYP51 proteins. This is the first report of the existence of two homologue genes coding for 14-α sterol demethylase in the fungal kingdom. This finding could provide insights into the azole resistance mechanisms operating in fungi. The primers used here may be useful molecular tools for facilitating the cloning of novel 14-α sterol demethylase genes in other filamentous fungi.